Acceleration Of Rate Of Oxidation Of Ferrous Iron In Presence Of Copper, And Its Application To "Heap Leaching" Process (AIME) - E. Posnjak (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1927)
IT is rather the general belief that acidified solutions of ferrous salts are readily oxidized when in contact with air, and often elaborate pre-cautions are taken to prevent it. This, however, is not the case and several statements may be found in the literature expressing surprise at the extreme slowness with which oxidation takes place when air or oxygen is bubbled through such a solution. Thus C. Baskerville and R. Stevenson1 "observed with surprise" that no. oxidation apparently took place, as shown by titration with 0.5 N KMnO4, when a stream of air was passed for 3 hr. through an acidified solution of ferrous ammonium sulfate or ferrous sulfate. The same authors state that even the presence of salts such as cobalt, chromium, copper, manganese, etc., which usually act as oxygen carriers, had "no effect upon the oxidation as was observed by, passing air for 3 hr. through solutions of Mohr's salt acidified with sulfuric acid." While this statement will be proved further on to be at least partly incorrect the slowness of the oxidation of ferrous salts alone has been previously established by McBain.2. His investigation also showed that the rate of oxidation increases markedly with an increase in the concentration of ferrous sulfate as well as that of oxygen; the concentration of free acid had a comparatively small influence, which in the case of sulfuric acid was to retard slightly the rate of reaction. More recently R. Thomas and E. T. Williams3 investigated the catalytic effect of nitric oxide on the oxidation of ferrous salts, which had been earlier patented by McCulloch.4 They found that the probable mechanism of the catalytic action was the oscillation of the catalyst between two stages of oxidation and its interaction alternately with the oxygen and the ferrous iron.